Hydrostatic Message is an Effective Measure in Canalization of Congenital Naso- Lacrimal Duct Obstruction (Faridpur Medical College Journal, 2016)
Congenital nasolacrimal duct obstruction presented as watering from eye is often seen in ophthalmic practice. It is estimated that about 20% of newborn suffer from such condition. Out of this, 2-3% suffers from only watering but most of them suffer from both watering & discharge. Most cases of watering in the newborn are due to incomplete canalization of nasolacrimal duct, which is delayed due to unfavourable environment in the vicinity. It needs effective medical treatment to keep healthy environment to exacerbate the process of canalization. Treatment of nasolacrimal duct obstruction varies among physicians, as to timing & forms but highly successful in most cases but early treatment is important. About 95% cases can be cured by hydrostatic message and only 5% needs probing operation under general anesthesia. The aim of our study is to establish that hydrostatic message is an important treatment option for congenital nasolacrimal duct obstruction. This study was conducted in the department of Ophthalmology at Diabetic Association Medical College & Hospital, Faridpur, from January 2012 to December 2014. A total 100 cases of newborn baby of watering with or without discharges were selected by random sampling. Age group ranges between 07 days to two years. Hydrostatic message was given to all of them after adequate training of hydrostatic message & its importance for the effective treatment to parents or the attendant. In addition, broad spectrum topical antibiotic drops and supportive medication was given. Patients were followed up 3 monthly for 2 years. In this study, 95 patients (95%) were cured. So, hydrostatic message is effective in canalization of congenital nasolacrimal duct obstruction.Faridpur Med. Coll. J. Jul 2015;10(2): 50-51